Production of Ultracold XOH (X = Ca, Sr, Ba) Molecules by Direct Laser Cooling: A Theoretical Study Based on Accurate Ab Initio Calculations - Jingbo Wei; Peng Li; Jizhou Wu; Yuqing Li; Wenliang Liu; Yongming Fu; Jie Ma (Molecules)
Effective laser cooling schemes are fundamental for preparing ultracold triatomic molecules. Here, efficient laser cooling strategies for alkaline-earth hydroxides (XOH, X = Ca, Sr, Ba) are proposed using high-precision quantum calculations. By mapping Λ-S- and Ω-state potential energy surfaces, we identified quasi-closed optical cycles with dominant Franck–Condon factors (FCFs) and strong transition dipoles. The scheme utilizes targeted repumping to suppress vibrational leaks, enabling >104 photon scatters per molecule, exceeding Doppler cooling requirements. These results establish XOH molecules, particularly BaOH, as viable candidates for laser cooling experiments, providing key theoretical insights for ultracold triatomic molecule production.